Preparation method of graphite piece containing tantalum carbide coating

Through the preparation of slurry suspension and high-temperature sintering, a tantalum carbide coating with large grain size and porous structure was prepared, which solved the problem of easy corrosion of traditional graphite materials at high temperatures and achieved the tightness of the coating and graphite substrate. Combined with high temperature corrosion resistance, it is suitable for SiC crystal growth conditions at 2600℃.

CN119462207APending Publication Date: 2025-02-18ZHEJIANG LIUFANG CARBON TECH CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411697573.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional graphite materials are prone to corrosion at high temperatures of 2600℃. The grains of TaC coating grow and merge under long-term high temperature conditions, resulting in increased thermal stress and failure of coating. The existing process temperature is lower than 2300℃, which is difficult to meet. High temperature corrosion resistance needs.

Method used

Through the preparation of slurry suspension, graphite coating, and high-temperature sintering, a tantalum carbide coating with large grain size and porous structure was prepared. Iron powder was used as the sintering agent to control the mass ratio of TaC powder and sintering agent to be 60: 4. Optimize the sintering temperature and time to form a spherical stacked tantalum carbide coating.

Benefits of technology

The tantalum carbide coating is closely combined with graphite substrate, which improves the corrosion resistance and service life of the coating, reduces production costs, and is suitable for SiC crystal growth conditions at 2600℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005154054270000011
    Figure HDA0005154054270000011
  • Figure HDA0005154054270000012
    Figure HDA0005154054270000012
  • Figure HDA0005154054270000013
    Figure HDA0005154054270000013
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductors, in particular to a preparation method of a graphite piece containing a tantalum carbide coating, which at least comprises the following steps: preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersing agent and an adhesive; coating the surface of a graphite piece with the slurry suspension, and drying to form a pre-coating layer; the pre-coating layer is subjected to high-temperature sintering, the tantalum carbide coating layer is formed after natural cooling, the grain size of the tantalum carbide coating layer is 30-90 microns, the tantalum carbide coating layer graphite piece which is high in bonding strength, large in grain size and of a porous structure is obtained through slurry suspension preparation, graphite coating and high-temperature sintering, operation is easy, the production cost is low, and the actual application requirement is better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, in particular to a method for preparing a graphite part containing a tantalum carbide coating. Background Art

[0002] In the PVT (physical vapor transport) method of growing SiC (silicon carbide) single crystal ingots, the graphite materials and carbon-carbon composite materials in traditional thermal field materials are difficult to withstand the long-term corrosive atmosphere (Si, SiC2, Si2C) at 2600℃. Different thermal field components are replaced every one to ten furnaces, and the life is short. In addition, the dialysis and volatilization of graphite at high temperatures easily lead to the formation of crystal defects such as carbon inclusions. High-quality TaC coated parts must have better service life and cost than traditional thermal field materials under actual working conditions, such as graphite, carbon-carbon composite, SiC coated graphite parts, pBN (pyrolytic boron nitride) coatings, and alloy parts. Therefore, the most important technical problem to be solved is how many furnaces (various manufacturers) the TaC coating can effectively protect the base graphite from corrosion (that is, the coating does not peel off, there are no cracks, bulges, and is not corroded). The thickness, crystal orientation, grain size, density (whether there are cracks or holes), and the difference in thermal expansion coefficient between the substrate and the coating of the TaC coating will affect the service life of the coating. Especially under SiC crystal growth conditions (2600°C), the difference in thermal expansion coefficients between the substrate and the coating can easily produce large thermal stress and cause coating peeling.

[0003] Therefore, CVD-TaC coated graphite parts have not completely replaced traditional silicon carbide coated graphite materials. How to enhance the chemical bonding between the coating and the substrate and increase the service life of the coated parts under actual working conditions, improve production efficiency (one furnace for multiple firings) and reduce production costs (simple production) for the optimization of thermal field components in the crystal growth and epitaxy of the third-generation semiconductors (SiC, AlN, GaN) is a problem that needs to be solved urgently. For example, the method and graphite device for preparing tantalum carbide coating on the surface of graphite substrate disclosed in the Chinese patent application use tantalum pentachloride as tantalum source and carbon on the surface of graphite substrate as carbon source. Through the reaction of the two and hydrogen, tantalum carbide coating can be generated in situ on the surface of graphite substrate, so as to achieve the close bonding between tantalum carbide coating and graphite substrate. However, under the long-term high temperature crystal growth condition of 2600°C, TaC grains will inevitably grow and merge, and thermal stress will increase sharply. Therefore, the small-sized tantalum carbide porous structure and low-melting-point gradient composite coating are very easy to fail. SiC vapor will be generated in the composite coating SiC / TaC, which will corrode the coating from the inside; the thin layer of Ta in the buffer layer Ta / TaC will bend and deform. The process temperature of preparing TaC coating by CVD method, molten salt method, precursor conversion method, etc. is usually lower than 2300℃, and the coating prepared by plasma spraying has a Ta2O5 oxide layer with a lower melting point, which is easy to introduce impurities into the SiC crystal growth. Therefore, how to produce a tantalum carbide coating that is tightly bonded to the graphite matrix and increase the service life of the coated parts under actual working conditions, improve production efficiency (multiple firings in one furnace) and reduce production costs is crucial to the semiconductor field. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a graphite part containing a tantalum carbide coating, wherein a tantalum carbide coated graphite part with high bonding strength, large grain size and porous structure is obtained through slurry suspension preparation, graphite coating and high-temperature sintering. The method has simple operation, low production cost and better meets the actual application needs.

[0005] In one aspect, the present invention provides a method for preparing a graphite part containing a tantalum carbide coating, which comprises at least the following steps:

[0006] Preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and a binder;

[0007] Applying the slurry suspension to the surface of the graphite piece and drying to form a pre-coating layer;

[0008] The pre-coating layer is sintered at a high temperature and then naturally cooled to form a tantalum carbide coating layer, wherein the grain size of the tantalum carbide coating layer is 30 μm-90 μm.

[0009] As a preferred technical solution, the tantalum source includes at least one of Ta2O5, Ta powder, TaOC interionic compound, and TaC powder; the carbon source includes at least one of C powder, acetylacetone, and TaC powder.

[0010] Preferably, the tantalum source and the carbon source are both TaC powder.

[0011] Preferably, the purity of the TaC powder is 99.99 wt %, and the particle size is 100 nm-2000 nm, preferably 800 nm-1200 nm.

[0012] As an example, the particle size of the TaC powder may be 800 nm, 900 nm, 1000 nm, or 1200 nm.

[0013] At present, in order to ensure the high quality and stable growth of SiC crystals, and considering the cost of industrial production, ultra-high temperature corrosion-resistant ceramic coatings are prepared on the surface of graphite parts, which will extend the life of graphite components, inhibit impurity migration and improve crystal purity. In SiC epitaxial growth, silicon carbide coated graphite bases are usually used to support and heat single crystal substrates. Their service life is still effective, and silicon carbide deposits on the interface need to be cleaned regularly. In contrast, tantalum carbide (TaC) has a melting point of up to 3880°C and has better chemical inertness and thermal stability to ammonia, hydrogen, and silicon-containing vapor at high temperatures. Increasing the service life of TaC coated parts by selecting graphite with a high thermal expansion coefficient (high cost), constructing a buffer coating between the coating and the substrate, preparing a high melting point TaC composite coating, and preparing a TaC multilayer structure still cannot simultaneously meet the actual application requirements of low cost, high bonding strength, and high service life.

[0014] The method provided in the present application adopts TaC powder instead of the traditional mixed powder of tantalum source and carbon source, thereby avoiding the problem of reduced coating life due to uneven powder dispersion and easy sublimation of Ta2O5, which is beneficial to subsequent coating thickness control and sintering thickness control.

[0015] As a preferred technical solution, the sintering agent includes at least one of chromium (Cr), nickel (Ni), cobalt (Co), tantalum (Ta), and iron (Fe), and iron (Fe) is most preferred.

[0016] As a preferred technical solution, the purity of the sintering agent is 99.99wt%, and the particle size is 500nm-2000nm, preferably 800nm-1200nm.

[0017] As an example, the particle size of the sintering agent may be 800 nm, 900 nm, 1000 nm, or 1200 nm.

[0018] As a preferred technical solution, the mass ratio of the TaC powder to the sintering agent is (40-70):(1-10), preferably (50-70):(1-5), more preferably 60:(1-5), and most preferably 60:4.

[0019] As an example, the mass ratio of the TaC powder to the sintering agent may be 60:1, 60:2, 60:3, 60:4, or 60:5.

[0020] Furthermore, the present invention effectively controls the grain size and porosity of the TaC coating by optimizing the type, size, content and sintering temperature of the sintering agent. The recrystallization growth process of the sintered tantalum carbide allows the coating to be tightly combined with the graphite substrate and densely fills the graphite pores, thereby improving the corrosion resistance of the coating.

[0021] In particular, iron powder is used as a sintering agent, and the mass ratio of TaC powder and sintering agent is further controlled to be 60:4. The subsequently formed large-grained, porous tantalum carbide coating can reduce the mismatch and cracking problems with the graphite substrate caused by the increase in grain size under the SiC crystal growth condition of 2600°C. In addition, under the repeated heating and cooling process, the spherical structure and porous structure of the tantalum carbide coating can effectively release thermal stress, thereby increasing the service life of the graphite coating components and reducing the production cost. The inventors analyzed that the reasons may be: the sintering agent can lower the sintering melting point and catalytic reaction. Under the method provided by the present invention, iron with a melting point of about 1500°C-1550°C has a good sintering effect compared with metal sintering agents such as chromium, nickel, cobalt, tantalum, etc. with the same content ratio. The formed tantalum carbide coating has a larger grain size. As the mass ratio of TaC:Fe decreases, the grains of the formed tantalum carbide coating gradually change from step fine crystals to large-sized spheres, and the pores increase. When the mass ratio of TaC:Fe is ≤60:5, the free carbon in the slurry and the carbon on the surface of the graphite will diffuse to the top layer of the TaC coating during the high-temperature sintering process.

[0022] As a preferred technical solution, the dispersant is selected from at least one of anhydrous ethanol, deionized water, ethylene glycol, methanol, and isopropanol, preferably anhydrous ethanol.

[0023] As a preferred technical solution, the adhesive includes at least one of polyvinyl butyral, polyvinyl alcohol, polyacrylamide, polyethylene oxide, phenolic resin, and graphite glue, preferably polyvinyl butyral.

[0024] Preferably, the weight average molecular weight (M W ) is 50000-120000, preferably 70000-90000.

[0025] As a preferred technical solution, the weight ratio of the dispersant to the total weight of the TaC powder and the sintering agent is (3-6):1, preferably 4:1.

[0026] As an example, the weight ratio of the dispersant to the total weight of the TaC powder and the sintering agent may be 3:1, 4:1, 5:1, or 6:1.

[0027] As a preferred technical solution, the mass proportion of the binder in the slurry suspension is 1%-5%, preferably 2%-4%, and most preferably 3%.

[0028] As an example, the mass proportion of the binder in the slurry suspension may be 2%, 2.5%, 3%, 3.5%, or 4%.

[0029] As a preferred technical solution, the step of configuring a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and a binder includes: mixing the tantalum source, the carbon source, and the sintering agent and then subjecting them to ball milling treatment, then stirring and mixing with the dispersant and the binder, stirring and mixing until there are no particles, and then subjecting them to ultrasonic treatment to obtain a slurry suspension.

[0030] Preferably, the apparatus for ball milling is a ball mill, and the apparatus for ultrasonic treatment is an ultrasonic cell crusher.

[0031] Preferably, the rotation speed of the ball milling treatment is 200 r / min-1000 r / min, and the time of the ball milling treatment is 5 h-12 h.

[0032] Preferably, the rotation speed of the ball milling treatment is 500 r / min-1000 r / min, and the time of the ball milling treatment is 5 h-10 h.

[0033] As an example, the rotation speed of the ball milling treatment can be 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, and the time of the ball milling treatment can be 5h, 6h, 7h, 8h, 9h, 10h.

[0034] Preferably, the conditions for the ultrasonic treatment are: the amplitude of the horn is 20, the frequency is 15KHz-35KHz, the power is 1000W-1500W, and the ultrasonic time is 20min-60min.

[0035] Preferably, the conditions of the ultrasonic treatment are: the amplitude of the horn is 20, the frequency is 20.5 KHz, the power is 1200 W, and the ultrasonic time is 30 min.

[0036] Preferably, the particle size of the powder in the slurry suspension is less than 200 nm.

[0037] In the subsequent coating process of the slurry suspension in the present invention, a secondary ultrasonic treatment is required every 30 minutes (the conditions of the secondary ultrasonic treatment are: the amplitude of the horn is 20, the frequency is 20.5KHz, the power is 1200W, and the ultrasonic time is 3 minutes) to ensure the uniformity of the slurry suspension.

[0038] The invention adopts TaC powder and iron powder with a particle size of 800nm-1200nm, mixes the TaC powder and the iron powder and then performs ball milling, and then cooperates with ultrasonic treatment under the action of a certain amount of added binder to achieve uniform dispersion of the TaC powder and the iron powder in a dispersant, without sedimentation processes such as flocculation and agglomeration, and without obvious stratification (i.e., no upper layer of dispersant clear liquid) after standing for 30min-60min.

[0039] As a preferred technical solution, the step of applying the slurry suspension to the surface of the graphite part and drying to form a pre-coating layer includes: applying the slurry suspension to the surface of the graphite part, placing it in a vacuum drying oven after natural drying, and keeping it at 150℃-250℃ for 8h-16h to form a pre-coating layer.

[0040] As a preferred technical solution, the graphite piece is obtained by the following method: high-purity graphite is cut to obtain a graphite block, the surface of the graphite block is polished smooth using 100 mesh, 220 mesh, 400 mesh, and 800 mesh sandpaper in sequence, and the graphite block is placed in alcohol for ultrasonic cleaning. After cleaning, the graphite block is placed in a vacuum drying oven, and the graphite piece is obtained after being dried at 200°C for 2h-12h.

[0041] As a preferred technical solution, the coating method includes one of vacuum infiltration, spraying (ultrasonic spraying), flow coating, and brushing, preferably flow coating.

[0042] TaC coated graphite parts include: crucibles, seed crystal holders, and guide rings in the PVT method for growing SiC and AlN single crystal furnaces; heaters in MOCVDGaN epitaxial layer growth; wafer carriers, baffles, external floating air nozzles, air guides, pneumatic ducts, etc. in SiC epitaxy. Since the above graphite parts have different shapes and sizes, the coating process matches the corresponding vacuum infiltration, spraying (ultrasonic spraying), curtain coating, and brushing for slurry suspension coating.

[0043] As a preferred technical solution, the thickness of the pre-coating layer is 50 μm-500 μm, preferably 100 μm-200 μm.

[0044] The present invention controls the addition amount of each raw material in the slurry suspension and controls the thickness of the pre-coat layer to be 100μm-500μm, so as to form a pre-coat layer with a relatively uniform, flat and dense surface without cracks and bulges. If the pre-coat layer is too thin, it cannot completely cover the graphite substrate, and if it is too thick, a large number of holes and cracks will appear after drying due to volume shrinkage.

[0045] As a preferred technical solution, the temperature of the high-temperature sintering is ≥2300°C, and the time of the high-temperature sintering is 0.5h-3h.

[0046] Preferably, the temperature of the high temperature sintering is 2300° C.-2600° C., and the time of the high temperature sintering is 2 hours.

[0047] At present, the TaC coatings prepared by the CVD method and other means are all tightly stacked on graphite. Due to the inconsistent thermal expansion coefficients between the coating and the graphite substrate, when the temperature changes, including high temperature heating and natural cooling processes (the application temperature of the TaC coating is 2600°C), the restricted expansion process and recrystallization process that occur will make the interface very easy to bend, debond, and delaminate, so that the cracks penetrate and penetrate the entire coating channel. Therefore, the tantalum carbide coating formed by the method of the present invention is spherically stacked, the grain size is controllable at 5-80μm, and there are certain pores (within 5μm) between each grain, which effectively overcomes the above problems. The preferred sintering temperature is 2500℃-2600℃, and the sintering time is 30min-60min. The sintering agent can reduce the reaction temperature point, and the large-size TaC coating sintered at more than 2600℃ can be better suitable for SiC crystal growth conditions. However, too high a sintering temperature will cause the graphite to permeate and crystallize on the surface of the coating, causing the TaC ratio to shift in stoichiometric ratio. High temperature annealing at 2600℃ will cause small-sized TaC to recrystallize, grow, merge, and shrink ( Figure 8 ), which can easily lead to cracking and peeling of the coating ( Fig. 9 The large-sized, porous TaC coating of the present invention can be sintered at 2600°C for 24 hours and still maintain a good appearance.

[0048] On the other hand, the present invention provides a method for preparing a spherical double-layer tantalum carbide coating on the surface of a graphite part, which specifically comprises the following steps: tantalum powder (purity 99.99%, particle size 10nm-20nm), anhydrous ethanol, and polyvinyl butyral (PVB) are mixed into a uniform and stable secondary coating suspension by stirring, ultrasonication, and centrifugation, wherein PVB accounts for 2%-8% of the total weight of the secondary coating suspension, anhydrous ethanol accounts for 70%-80% of the total weight of the secondary coating suspension, and tantalum powder accounts for 15%-30% of the total weight of the secondary coating suspension; a pre-coating layer with a thickness of 5μm-20μm is coated on the formed tantalum carbide coating, and after drying, sintering is performed in a vacuum environment of 1Pa-3Pa, wherein the sintering temperature is ≥2300°C, the sintering time is 0.1h-1h, and the spherical double-layer tantalum carbide coating is obtained after natural cooling.

[0049] During the research process, the present invention found that the surface of the tantalum carbide coating has many pores and is not dense enough in the corrosive atmosphere of SiC crystal growth. The surface of the tantalum carbide coating can be used to prepare a second dense layer by slurry sintering. The purity of the second TaC coating is crucial to SiC crystal growth and impurities cannot be introduced. The preferred impurity concentration of the TaC coating needs to be less than 10ppm. Therefore, the present invention first applies a layer of high-purity tantalum powder on the first layer of TaC with large grains, and carbonizes it through saturated graphite vapor in a graphite crucible at high temperature to generate a high-purity TaC dense layer. Experiments have found that the tantalum layer can be more evenly carbonized under a vacuum environment.

[0050] Beneficial Effects

[0051] 1. The present invention provides a method for preparing a graphite part containing a tantalum carbide coating, wherein a tantalum carbide coated graphite part with high bonding strength, large grain size and porous structure is obtained by slurry suspension preparation, graphite coating and high temperature sintering. The method has simple operation, low production cost and better meets the actual application requirements.

[0052] 2. The present invention effectively controls the grain size and porosity of the TaC coating by optimizing the type, size, content and sintering temperature of the sintering agent. The recrystallization growth process of the sintered tantalum carbide makes the coating tightly combined with the graphite substrate and densely fills the graphite pores, thereby improving the corrosion resistance of the coating.

[0053] 3. The present invention adopts iron powder as a sintering agent and further controls the mass ratio of TaC powder and sintering agent to 60:4. The subsequently formed large-grained, porous tantalum carbide coating can reduce the problems of mismatch and cracking with the graphite substrate caused by the increase in grain size under the SiC crystal growth condition of 2600°C. In addition, under the repeated heating and cooling process, the spherical structure and porous structure of the tantalum carbide coating can effectively release thermal stress, thereby increasing the service life of the graphite coating components and reducing the production cost.

[0054] 4. The present invention adopts TaC powder and iron powder with a particle size of 800nm-1200nm, mixes the TaC powder and the iron powder and then ball-mills them, and then adds a certain amount of binder and ultrasonic treatment to achieve uniform dispersion of the TaC powder and the iron powder in the dispersant, without flocculation and agglomeration and other sedimentation processes, and no obvious stratification occurs (i.e., no upper layer of dispersant clear liquid) after standing for 30min-60min.

[0055] 5. The present invention controls the addition amount of each raw material in the slurry suspension and controls the thickness of the pre-coating layer to be 100μm-500μm, thereby forming a pre-coating layer with a relatively uniform, flat and dense surface without cracks and bulges. If the pre-coating layer is too thin, it cannot completely cover the graphite substrate, and if it is too thick, a large number of holes and cracks will appear after drying due to volume shrinkage.

[0056] 6. The tantalum carbide coating formed by the method of the present invention is spherically stacked, with a controllable grain size of 5μm-80μm, and certain pores (within 5μm) between the grains. It can maintain a good appearance after sintering at 2600°C for 24 hours, and is better suitable for SiC crystal growth conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a SEM characterization image of the tantalum carbide coating formed in Example 1, with the left side of the image showing the coating surface and the right side showing a cross-sectional image of the coating.

[0058] Figure 2 This is a SEM characterization image of the spherical double-layer tantalum carbide coating formed in Example 2. The left side of the image is a cross-sectional view of the coating, and the right side is an enlarged cross-sectional view of the coating.

[0059] Figure 3 This is a SEM characterization image of the tantalum carbide coating formed in Comparative Examples 1-4, where ad in the image corresponds to Comparative Examples 1-4, respectively.

[0060] Figure 4 This is a SEM characterization image of the tantalum carbide coating formed in Comparative Examples 5-8, where ad in the image corresponds to Comparative Examples 5-8, respectively.

[0061] Figure 5 This is a SEM characterization picture of the pre-coating layer formed in Comparative Example 9.

[0062] Figure 6 This is a SEM characterization picture of the pre-coating layer formed in Comparative Example 10.

[0063] Figure 7 This is a SEM characterization picture of the pre-coating layer formed in Comparative Example 11.

[0064] Figure 8 The high temperature annealing at 2600℃ causes the recrystallization growth, merging and shrinkage of small-sized TaC.

[0065] Fig. 9 The SEM images and appearance pictures of the peeled coating. DETAILED DESCRIPTION

[0066] The present invention optimizes the type and content of the sintering agent and the thickness of the pre-coating layer, so that the formed tantalum carbide coating is spherically stacked, the grain size is controllable at 5-80 microns, and there are certain pores (within 5 μm) between each grain. The recrystallization growth process of the sintered tantalum carbide makes the coating closely combined with the graphite substrate and densely fills the graphite pores, which can reduce the mismatch and cracking problems caused by the increase of the grain size with the graphite substrate under the SiC crystal growth condition of 2600°C. In addition, under the repeated heating and cooling process, the spherical structure and porous structure of the tantalum carbide coating can effectively release thermal stress, thereby making the life of the graphite coating parts longer and the production cost lower.

[0067] Example 1

[0068] Embodiment 1 of the present invention provides a method for preparing a graphite part containing a tantalum carbide coating, comprising the following steps:

[0069] Preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and a binder;

[0070] Applying the slurry suspension to the surface of the graphite piece and drying to form a pre-coating layer;

[0071] The pre-coating layer is sintered at a high temperature and then naturally cooled to form a tantalum carbide coating layer.

[0072] The tantalum source and the carbon source are both TaC powder.

[0073] The purity of the TaC powder is 99.99wt%, and the particle size is 1000nm, Beijing Yanbang New Material Technology Co., Ltd.

[0074] The sintering agent is iron (Fe) powder.

[0075] The purity of the sintering agent is 99.99wt%, and the particle size is 1000nm, Jiangxi Guocai Technology Co., Ltd.

[0076] The mass ratio of the TaC powder to the sintering agent is 60:4.

[0077] The dispersant is anhydrous ethanol.

[0078] The adhesive is polyvinyl butyral.

[0079] The weight average molecular weight (M W ) is 70000-90000.

[0080] The weight ratio of the dispersant to the total weight of the TaC powder and the sintering agent is 4:1.

[0081] The mass proportion of the binder in the slurry suspension is 3%.

[0082] The steps of preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and an adhesive include: mixing the tantalum source, the carbon source, and the sintering agent and then subjecting them to ball milling treatment, then stirring and mixing with the dispersant and the adhesive, stirring and mixing until there are no particles, and then placing in an ultrasonic cell crusher for ultrasonic treatment to obtain a slurry suspension.

[0083] The apparatus for ball milling is a ball milling jar;

[0084] The rotation speed of the ball milling treatment is 600 r / min, and the time of the ball milling treatment is 8 h.

[0085] The conditions of the ultrasonic treatment are: the amplitude is 20, the frequency is 20.5KHz, the power is 1200W, and the ultrasonic time is 30min.

[0086] The particle size of the powder in the slurry suspension is less than 200 nm.

[0087] In the subsequent coating process of the slurry suspension in the present invention, a secondary ultrasonic treatment is required every 30 minutes (the conditions of the secondary ultrasonic treatment are: the amplitude of the horn is 20, the frequency is 20.5KHz, the power is 1200W, and the ultrasonic time is 3 minutes) to ensure the uniformity of the slurry suspension.

[0088] The step of applying the slurry suspension to the surface of the graphite piece and drying to form a pre-coating layer comprises: applying the slurry suspension to the surface of the graphite piece, naturally drying it, placing it in a vacuum drying oven, and keeping it at 200° C. for 12 hours to form a pre-coating layer.

[0089] The graphite piece is obtained by the following method: high-purity graphite is cut to obtain a 10mm*10mm*2mm ink block, 100-mesh, 220-mesh, 400-mesh, and 800-mesh sandpapers are used to polish the surface of the graphite block, and the graphite block is placed in alcohol for ultrasonic cleaning. After cleaning, the graphite block is placed in a vacuum drying oven, and the graphite piece is obtained after the graphite block is dried at 200°C for 10 hours.

[0090] The coating method is shower coating.

[0091] The thickness of the pre-coating layer is 150 μm.

[0092] The high temperature sintering temperature is 2300° C., and the high temperature sintering time is 2 hours.

[0093] The maximum grain size of the tantalum carbide coating is 50 μm and the coating thickness is 129 μm (see Figure 1 ).

[0094] Example 2

[0095] Embodiment 2 of the present invention provides a method for preparing a spherical double-layer tantalum carbide coating on the surface of a graphite part, which specifically comprises the following steps: tantalum powder (purity 99.99%, diameter 10nm), anhydrous ethanol, and polyvinyl butyral (PVB) are stirred, ultrasonicated, and centrifuged to form a uniform and stable secondary coating suspension, wherein PVB accounts for 5% of the total weight of the secondary coating suspension, anhydrous ethanol accounts for 75% of the total weight of the secondary coating suspension, and tantalum powder accounts for 20% of the total weight of the secondary coating suspension; a pre-coating layer with a thickness of 10μm is applied on the tantalum carbide coating formed in Embodiment 1, and after drying, it is sintered in a vacuum environment of 2Pa, the sintering temperature is 2300°C, the sintering time is 0.5h, and after natural cooling, a spherical double-layer tantalum carbide coating is obtained (see Figure 2 ).

[0096] Comparative Example 1

[0097] Comparative Example 1 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:1, and the sintering agent is replaced by Cr powder (99.99wt%, particle size 1000nm, Suzhou Youyan New Materials Industrial Co., Ltd.). The formed tantalum carbide coating is shown in Figure 3 (a).

[0098] Comparative Example 2

[0099] Comparative Example 2 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:1, and the sintering agent is replaced by Ni powder (99.99wt%, particle size 1000nm, Jiangxi Guocai Technology Co., Ltd.). The formed tantalum carbide coating is shown in Figure 3 (b).

[0100] Comparative Example 3

[0101] Comparative Example 3 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:1, and the sintering agent is replaced by Co powder (99.99wt%, particle size 1000nm, McLean), and the formed tantalum carbide coating is shown in FIG. Figure 3 (c).

[0102] Comparative Example 4

[0103] Comparative Example 4 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:1, and the sintering agent is replaced by Ta powder (99.99wt%, particle size of 1000nm, McLean), and the formed tantalum carbide coating is shown in FIG. Figure 3 (d).

[0104] Comparative Examples 1-4 changed the type of sintering agent, and the grain size of the prepared tantalum carbide coating did not reach the effect in Example 1. The replacement of Cr and Ni not only failed to achieve a larger grain size at this mass ratio, but also resulted in many holes in the coating as a whole, large cracks, low density, and easy peeling from the graphite substrate; the replacement of Co and Ta can promote the densification of the coating, that is, when used as a conventional sintering agent, the morphology of the prepared TaC coating is similar to that of the CVD-TaC coating, and the densification effect of Co is not as good as that of Ta. It can be seen that optimizing the selection of sintering agents and the control of grain structure are crucial to improving the performance of tantalum carbide coatings.

[0105] Comparative Example 5

[0106] Comparative Example 5 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:1, and the formed tantalum carbide coating is as shown in FIG. Figure 4 (a).

[0107] Comparative Example 6

[0108] Comparative Example 6 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:2, and the formed tantalum carbide coating is as shown in FIG. Figure 4 (b).

[0109] Comparative Example 7

[0110] Comparative Example 7 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:3, and the formed tantalum carbide coating is shown in FIG. Figure 4 (c).

[0111] Comparative Example 8

[0112] Comparative Example 8 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the mass ratio of the TaC powder to the sintering agent is 60:5, and the formed tantalum carbide coating is as shown in FIG. Figure 4 (d).

[0113] From Comparative Examples 5-8, it can be seen that with the increase of Fe content, the grain size of TaC coating increases in a positive correlation. This trend shows that the introduction of Fe plays a positive role in promoting grain growth. During high-temperature sintering, Fe can fill the gaps between grains in a molten state, thereby effectively reducing the interfacial energy of the particles. This effect of reducing interfacial energy promotes the merging and growth of grains, resulting in the final formation of larger grains. In practical applications, larger grain size is usually associated with better mechanical properties and wear resistance.

[0114] Comparative Example 9

[0115] Comparative Example 9 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the thickness of the pre-coating layer is 600 μm. Figure 5 , do not proceed to the next steps.

[0116] Comparative Example 10

[0117] Comparative Example 10 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the thickness of the pre-coating layer is 700 μm. Figure 6 , do not proceed to the next steps.

[0118] Comparative Example 11

[0119] Comparative Example 11 of the present invention provides a method for preparing a tantalum carbide coating on the surface of a graphite part. The specific implementation method is the same as that of Example 1, except that the thickness of the pre-coating layer is 1000 μm. Figure 7 , do not proceed to the next steps.

[0120] From Comparative Examples 9-11, we observed that excessive increase in pre-coating thickness can lead to a series of unfavorable phenomena, including particle accumulation, cracks and peeling. These problems are particularly evident in the dried pre-coating, which directly affects the subsequent sintering effect. Too thick a pre-coating can lead to insufficient interaction and bonding between particles. During the sintering process, the excessive thickness of the pre-coating increases the distance between the particles, reducing the effective contact area between the particles. This insufficient contact leads to poor gas discharge during the sintering process, thereby increasing the porosity in the coating and forming a particle accumulation phenomenon. In addition, the thick coating will also be subjected to uneven heat conduction under high temperature conditions, which will lead to the generation of temperature gradients, further exacerbating the formation of cracks. The appearance of cracks not only affects the overall structural integrity of the coating, but also reduces its mechanical properties. These cracks will become the starting point of stress concentration and failure of the material during use, thereby affecting the wear resistance and corrosion resistance of the coating. Therefore, the optimal pre-coating thickness is sought to ensure good bonding between particles and effective gas discharge to achieve high-performance TaC coating preparation.

Claims

1. A method for preparing a graphite part containing a tantalum carbide coating, characterized in that: At least the following steps are included: Preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and a binder; Applying the slurry suspension to the surface of the graphite piece and drying to form a pre-coating layer; The pre-coating layer is sintered at a high temperature and then naturally cooled to form a tantalum carbide coating layer, wherein the grain size of the tantalum carbide coating layer is 30 μm-90 μm.

2. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The tantalum source includes at least one of Ta2O5, Ta powder, TaOC interionic compound, and TaC powder; the carbon source includes at least one of C powder, acetylacetone, and TaC powder.

3. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The sintering agent includes at least one of chromium, nickel, cobalt, tantalum and iron.

4. The method for preparing a graphite part containing a tantalum carbide coating according to claim 2, characterized in that: The mass ratio of the TaC powder to the sintering agent is (40-70):(1-10).

5. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The particle size of the TaC powder is 100nm-2000nm, and the particle size of the sintering agent is 500nm-2000nm.

6. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The dispersant includes at least one of anhydrous ethanol, deionized water, ethylene glycol, methanol, and isopropanol.

7. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The adhesive includes at least one of polyvinyl butyral, polyvinyl alcohol, polyacrylamide, polyethylene oxide, phenolic resin and graphite glue.

8. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The steps of preparing a slurry suspension containing a tantalum source, a carbon source, a sintering agent, a dispersant, and an adhesive include: mixing the tantalum source, the carbon source, and the sintering agent, performing ball milling, then stirring and mixing with the dispersant and the adhesive, stirring and mixing until there are no particles, and then performing ultrasonic treatment to obtain a slurry suspension.

9. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The step of applying the slurry suspension to the surface of the graphite part and drying to form a pre-coating layer comprises: applying the slurry suspension to the surface of the graphite part, placing it in a vacuum drying oven after natural drying, and keeping it at 150°C-250°C for 8h-16h to form a pre-coating layer, wherein the thickness of the pre-coating layer is 50μm-500μm.

10. The method for preparing a graphite part containing a tantalum carbide coating according to claim 1, characterized in that: The temperature of the high temperature sintering is ≥2300° C., and the time of the high temperature sintering is 0.5 h-3 h.

Citation Information

Cited By

  • Tantalum carbide coating, preparation method thereof and tantalum carbide product

    CN120229970A

  • Tantalum carbide coating and method of making same, tantalum carbide article

    CN120229970B

  • Method for eliminating carbon adsorbed on surface of carbide coating

    CN120398579A

  • A method for eliminating carbon adsorbed on the surface of carbide coatings

    CN120398579B

  • TaC coating and preparation method thereof, crucible containing TaC coating and application

    CN121021199A